Monocular inhibition reveals temporal and spatial changes in gene expression in the primary visual cortex of marmoset - Nakagami, Yuki; Watakabe, Akiya; Yamamori, Tetsuo (Frontiers in Neural Circuits, 2013)
We investigated the time course of the expression of several activity-dependent genes evoked by visual inputs in the primary visual cortex (V1) in adult marmosets. In order to examine the rapid time course of activity-dependent gene expression, marmosets were first monocularly inactivated by tetrodotoxin (TTX), kept in darkness for two days, and then exposed to various length of light stimulation. Activity-dependent genes including HTR1B, HTR2A, whose activity-dependency were previously reported by us, and well-known immediate early genes (IEGs), c-FOS, ZIF268, and ARC, were examined by in situ hybridization. Using this system, first, we demonstrated the ocular dominance type of gene expression pattern in V1 under this condition. IEGs were expressed in columnar patterns throughout layers II-VI of all the tested monocular marmosets. Second, we showed the regulation of HTR1B and HTR2A expressions by retinal spontaneous activity, because HTR1B and HTR2A mRNA expressions sustained a certain level regardless of visual stimulation and were inhibited by a blockade of the retinal activity with TTX. Third, IEGs dynamically changed its laminar distribution from half an hour to several hours upon a stimulus onset with the unique time course for each gene. The expression patterns of these genes were different in neurons of each layer as well. These results suggest that the regulation of each neuron in the primary visual cortex of marmosets is subjected to different regulation upon the change of activities from retina. It should be related to a highly differentiated laminar structure of primate visual systems, reflecting the functions of the activity-dependent gene expression in marmoset V1.